Primary Immunodeficiency and Cancer in Children; A Review of the Literature - Kebudi, Rejin (Curr Pediatr Rev, 2019)
The life span of patients with primary and secondary immunodeficiencies has increased due to recent advances in diagnostic and therapeutic strategies. Primary immune deficiencies (PIDs) are genetic disorders that predispose patients to frequent infections, autoimmunity and malignancies. Genomic instability due to defective DNA repair processes and other unknown mechanisms in patients with PID leads to an enhanced risk of cancer. PIDs were originally described as rare diseases occurring only in infants and young children, which are associated with severe clinical symptoms. However, advances in gene sequencing technologies, have revealed that they are much more common than originally appreciated and are present in older children, adolescents, and adults. After infection, malignancy is the most prevalent cause of death in both children and adults with PIDs. The overall risk of developing cancer in patients with PID is estimated to range from 4.7 to 5.7 percent. A 1.4 to 1.6-fold excess relative risk of cancer has been reported for PIDs. Increasing awareness among physicians regarding PID and cancer may lead to earlier diagnosis which may decrease morbidity and mortality. In this paper, we review the various categories of PIDs in children and highlight their association with various malignancies. MEDLINE was searched to identify articles for inclusion. Three authors have independently screened literature search results from MEDLINE and abstracted data from studies dealing with cancers of children among primary immune deficiencies.